Online learning in undergraduate medical education: Exploring students' preference on online learning tools and modes of learning / Nur Amirah Farhanah Hashim - Nur Amirah Farhanah, Hashim (2022)
The declaration of COVID-19 as a pandemic and Movement Control Order (MCO) had transformed the traditional face-to-face learning to online learning. During the pandemic, the online learning activities were conducted in students’ own learning environment. Therefore, this study aimed to explore the preferences of online learning tools and modes of learning among the undergraduate medical students using online learning during their preclinical studies. A qualitative study involving focus group discussions was conducted for this study. Undergraduate medical students of Faculty of Medicine, Universiti Malaya who are currently in Year 2 and Year 3 were recruited for the purpose of this study. Ethical approval was obtained prior to that, and the participants were recruited by approaching the students batch representatives using social media platform (i.e., WhatsApp, email). A total of thirty students participated in four focus group discussions. The discussions were conducted online using Microsoft Teams, and were video recorded. The data were analyzes using thematic analysis with the use of content analysis technique. The trustworthiness of the findings were done via credibility by giving the findings summary to the participants, while transferability was also ensured. Three themes were generated, namely: (i) Online learning tools, (ii) online learning modes, and (iii) concerns and areas of improvement for online learning implemented. Theoretical frameworks using self- regulated learning (SRL) and scaffolding concepts were used in addressing the research gaps found from the previous literatures, in order to answer the research questions of this study. The importance of SRL and scaffolding in online learning remains relevant, and thus modification required to suit with the learner needs in future settings. This study embarks on an improved quality of online learning for medical education to take place. Further investigation such as exploring the relationship between SRL and scaffolding in online learning may further enhance the findings generalizability.